2013
DOI: 10.1371/journal.pone.0068527
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Ezrin in Solid Tumors: A Meta-Analysis of the Literature

Abstract: PurposeEzrin is a cytoskeletal protein involved in tumor growth and invasion. However its prognostic value for survival in patients with solid tumor remains controversial.MethodsSeveral databases were searched, including Pubmed, Embase and Cochrane databases. The endpoints were overall survival (OS), progression-free survival (PFS). The pooled hazard ratio (HR) or odds ratio (OR), and 95% confidence intervals (CI) were calculated employing fixed- or random-effects models depending on the heterogeneity of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…However, the number of inclusion studies in the analysis was not relatively enough and at least 26 eligible studies were not included in the above meta-analysis, of which 8 studies about osteosarcomas were absolutely not included. Furthermore, the data reported by Han et al 68 for the study by Jörgren et al 69 were inconsistent with the data and the conclusion provided by Jörgren et al 69 in their original article. The HR value reported by Han et al 68 for OS is 1.89 (95% CI = 1.16–3.10), this suggested that high Ezrin expression was associated with worse prognosis in rectal cancer patients.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…However, the number of inclusion studies in the analysis was not relatively enough and at least 26 eligible studies were not included in the above meta-analysis, of which 8 studies about osteosarcomas were absolutely not included. Furthermore, the data reported by Han et al 68 for the study by Jörgren et al 69 were inconsistent with the data and the conclusion provided by Jörgren et al 69 in their original article. The HR value reported by Han et al 68 for OS is 1.89 (95% CI = 1.16–3.10), this suggested that high Ezrin expression was associated with worse prognosis in rectal cancer patients.…”
Section: Discussionmentioning
confidence: 78%
“…Furthermore, the data reported by Han et al 68 for the study by Jörgren et al 69 were inconsistent with the data and the conclusion provided by Jörgren et al 69 in their original article. The HR value reported by Han et al 68 for OS is 1.89 (95% CI = 1.16–3.10), this suggested that high Ezrin expression was associated with worse prognosis in rectal cancer patients. But after carefully studying the data presented by Jörgren et al 69 , we found Jörgren et al 69 just provided HR value about LR (local recurrence), not about OS.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Han et al emphasized that the ezrin expression was higher in many cancer types; however, Jörgren et al showed that the ezrin expression had no effect on the overall expression in the overall survival of the patients diagnosed with rectal cancer. [38,39,40] Ezrin, is a member of the protein family that normally binds the cellular skeleton ERM (ezrin, radixin, and moesin). [41] Ezrin occurs mainly in the inactive form in the cytoplasm, and it transforms to a special active form after the activation with treonin and tirosin phosphorylation.…”
Section: Treatment Of Osteosarcomamentioning
confidence: 99%